Rehabilitation of mutilated dentition associated with amelogenesis imperfecta - Bajracharya, A; Karn, SL; Shrestha, A (Journal of Nepalese Prosthodontic Society, 2021)
This clinical case report describes the oral rehabilitation of a young male with hypoplastic Amelogenesis Imperfecta with generalized hypoplastic and pitted teeth. All the teeth showed yellowish brown discoloration with rough irregular crowns. Patient was a young male who dissatisfied with his appearance and his condition degraded his confidence and psychology. Numerous treatment modalities have been described for rehabilitation of AI patient but the limitations in the treatment exists and the application of techniques are not universal The main objective of this selected treatment was to enhance the esthetics, restore masticatory function and eliminate the teeth sensitivity. These treatment objectives were successfully met by sequential approach. Treatment not only restored function and esthetic, but also showed a positive psychological impact and thereby improved perceived quality of life.